Frederick D. Patterson papers - Patterson, Frederick D. (Frederick Douglass), 1901-1988.
Correspondence, journal, speeches, writings, reports, notes, organizational records, clippings, printed matter, memorabilia, and other papers relating chiefly to Patterson's efforts, following his retirement as president of Tuskegee Institute in 1953, to preserve and develop African American institutions of higher learning. Documents his continued interest in Tuskegee Institute and the institute's School of Veterinary Medicine; his association with the Robert R. Moton Memorial Institute, the College Endowment Funding Plan, and the Phelps-Stokes Fund; and his inspection tour of educational resources in Nigeria (1953-1954). Includes transcripts of oral history interviews with Patterson (1980-1981). Subjects include George Washington Carver, civil rights, education in Africa, endowments, federal aid to higher education, Robert Russa Moton, segregation, and the South.
Correspondents include Robert L. Clayton, Nathaniel Sextus Colley, Luther H. Foster, E. Roland Harriman, Patricia Harris, Matthew Jenkins, Maida Springer Kemp, Benjamin E. Mays, Henry Lee Moon, Ponchitta Anne Pierce, Willa B. Player, Hollis F. Price, Robert Ogden Purves, Paul Simon, Caspar W. Weinberger, and Franklin Williams.
Library of Congress Prints and Photographs Division.
African American educational administrator and advocate.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carver, George Washington, -- 1864?-1943.; Clayton, Robert L. -- Correspondence; Colley, Nathaniel Sextus, -- 1918- -- Correspondence; Foster, Luther H. -- 1913- -- Correspondence; Harriman, E. Roland -- 1895-1978 -- Correspondence; Harris, Patricia, -- 1924-1985 -- Correspondence; Jenkins, Matthew -- Correspondence; Kemp, Maida Springer -- Correspondence; Mays, Benjamin E. -- 1894-1984 -- Correspondence; Moon, Henry Lee, -- 1901-1985 -- Correspondence; Moton, Robert Russa, -- 1867-1940.; Pierce, Ponchitta Anne, -- 1942- -- Correspondence; Player, Willa B. -- Correspondence; Price, Hollis F., -- 1904- -- Correspondence; Purves, Robert Ogden, -- 1895-1976 -- Correspondence; Simon, Paul, -- 1928-2003 -- Correspondence; Weinberger, Caspar W. -- Correspondence; Williams, Franklin, -- 1917- -- Correspondence; Phelps-Stokes Fund; Robert R. Moton Memorial Institute; Tuskegee Institute; Tuskegee Institute. -- School of Veterinary Medicine; African American universities and colleges; African Americans -- Civil rights; African Americans -- Education; Education -- Africa; Education -- Nigeria; Endowments -- United States; Federal aid to higher education; Segregation -- United States; Southern States; College administrators